Locust infestations now threaten Africa - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1986)
Two international organisations involved in controlling locust infestations in Africa have all but disappeared despite indications of a major upswing in locust populations. The Organisation to combat the African Migratory Locust (OICMA) was...